Nuaulu Settlement and Ecology - Ellen, R.F. (Brill, 1978)
This book is about the pattern of settlement and ecology of the Nuaulu, a group of sedentary swidden cultivators and hunters of southcentral Seram (Eastern Indonesia). It has three inter-related aims: to describe and account for nuaulu settlement; to outline and exemplify a suitable method of assessing the fine inter-action of cultural and ecological variables in small scale communities; and to explore the usefulness of a generative form of analysis in this respect.
English
Keywords: Asian history; indonesia; Ecology; Nuaulu people; Sago